Academic Dishonesty Among University Students: Gender, Semester Differences, and Influencing Factors - Renya Rosari; Anis Chariri; Dwi Cahyo Utomo (Emerging Science Journal, 2026)
This study examines differences in academic dishonesty among university students based on gender and semester level and identifies factors influencing such behavior using an explanatory sequential mixed-methods design. Quantitative data were collected from 405 undergraduate students across five semester levels (II, IV, VI, VIII, and X) using the Academic Dishonesty Scale (ADS) and analyzed with non-parametric statistical tests. The results show significant differences in examination-related cheating across semesters (p = 0.012) and significant gender differences across several indicators (p < 0.05), with male students and those in early semesters displaying higher levels of dishonest behavior. To further explain these findings, qualitative data were obtained through in-depth interviews with seven informants and analyzed thematically. The qualitative results indicate that academic dishonesty is influenced by pressure to achieve high grades, insufficient study preparation, permissive peer environments, and limited understanding of academic ethics. The novelty of this study lies in combining a validated measurement instrument with qualitative follow-up to provide contextual explanations of academic dishonesty in Indonesian higher education. The findings highlight the need for stricter supervision, strengthened academic ethics education, improved time management skills, and clearer institutional policies to foster an academic culture that promotes integrity.